A new genus of ovuliferous glossopterid fructifications from South Africa - Adendorff, R.; McLoughlin, S.; Bamford, M. K. (Bernard Price Institute for Palaeontological Research, 2002)
A new genus of Early Permian glossopterid fructifications, Gladiopomum, is established to accommodate pedicellate, capitate fructifications with narrow receptacles, apical spines, and very broad wings. Two species recognized within this genus were previously assigned to Scutum Plumstead and Hirsutum Plumstead, viz., G. dutoitides (Plumstead) comb. nov. and G. acadarense (Anderson & Anderson) comb. nov. An additional species, G. elongatum sp. nov. is established based on material from a new fossil locality at Rietspruit Colliery in the northern Karoo Basin. All species of Gladiopomum are confined to the Vryheid Formation; the genus may constitute a useful biostratigraphic index taxon for Artinskian strata throughout the Karoo Basin.
Main article
Keywords: Glossopterid; fructifications; South Africa